The use of energy-efficient and environmentally friendly materials in modern construction (Международный научный журнал «Инженер», 2026)
The article discusses current trends and innovative approaches in the field of energy-efficient and environmentally friendly materials in construction. Special attention is paid to the analysis of modern technological solutions aimed at reducing energy consumption and the carbon footprint of the construction industry. Key categories of such materials are described, including biocomposite thermal insulation solutions, geopolymer concretes, energy-efficient double-glazed windows, and wood-polymer composites. Their technological features, advantages, and impact on the sustainable development and environmental safety of construction are considered. The introduction of digital technologies and artificial intelligence into the design and production of building materials is discussed, which opens up new opportunities for optimizing production and increasing resource efficiency. The prospects for the further development of these technologies and their impact on the environmental and economic efficiency of the construction industry are analyzed. The presented data confirm the significant potential of modern innovative materials in implementing the concept of sustainable construction and reducing the negative impact on the environment.